Quantitative Fluorescence Determination of Long-Fragment DNA in Stool as a Marker for the Early Detection of Colorectal Cancer - Daniele Calistri; Claudia Rengucci; Chiara Molinari; Enrico Ricci; Elena Cavargini; Emanuela Scarpi; Gian Luigi Milandri; Carla Fabbri; Alberto Ravaioli; Antonio Russo; Dino Amadori; Rosella Silvestrini (Cellular Oncology)
Background: A variety of molecular markers have been evaluated for the development of a non-invasive approach to the diagnosis of colorectal cancer. We aimed to validate the diagnostic accuracy, using the same threshold as in the previous pilot study, of fluorescent long DNA test as a relatively simple and inexpensive tool for colorectal cancer detection.